Parle Agro (India) : vision realisation - Kaul, Asha, (SAGE Business cases., 2024)
Nadia Chauhan took charge of Parle Agro as Chief Marketing Officer (CMO) and Joint Managing Director (JMD) in 2009 where she had been working as a brand manager for Frooti since 2003, under the stewardship of her father, Prakash Chauhan. Under Chauhan's leadership, Parle Agro doubled its turnover to INR 50 billion between 2012 and 2017 following which, she proceeded to set an ambitious target of replicating the feat in the next five years (2022) to reach annual revenues of INR 100 billion. Within these five years, she wanted to become the dominant player in the beverage segment. The entry of major multi-national beverage companies in the Indian market presented a challenge for Parle Agro to ascend to the number one position. However, changing consumer preferences for healthy fruit drinks in different categories also provided an opportunity to experiment and expand. Reviewing the situation in 2019, Chauhan had to decide if Parle Agro should remain committed to the INR 100 billion target, upscale or mellow it down. Further, how should the company proceed—market penetration, product development, market development or diversification?